Between anti-westernism and development: political Islam and environmentalism. Issue 2 (3rd March 2016) - Yildirim, A. Kadir
ABSTRACT: As Turkey's Gezi Park protests reminded us, Islamist parties the world over demonstrate utter disregard of the environment in their discourse and actions. However, Islam as a religion places strong emphasis on environmental protection. Thus, as the representatives of Islam that these parties claim themselves to be, it is puzzling that environmental policy is all but absent from most Islamist platforms. I ask, what explains the poverty of Islamists in regards to the environment? I argue that the reason for this poverty is found within and conforms to political Islam's problematic relationship with modernity, particularly in regards to their strong anti-western sentiment and self-purported victim status. My findings suggest that the inattention Islamists give to the environment is due to their association of environmentalism with the West and because of the uniquely unfavourable socio-economic environments in which they exist, which sends environmentalism to the purview of 'low politics'. This analysis points to an inherent weakness in Islamist ideology – their lack of pragmatic policy. Hence, the peculiar case of Islamists and the environment is but a symptom of a larger issue within Islamism and can be a key element to understanding why and how Islamism is likely to fail.